2018
DOI: 10.1016/j.ultsonch.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

One-pot Sonochemical Synthesis of Hg–Ag Alloy Microspheres from Liquid Mercury

Abstract: Metallic mercury has always attracted much attention in various fields because of its unique characteristic of forming amalgams. Here, different phases of pure crystalline Hg-Ag amalgam microspheres are synthesized by ultrasonically reacting liquid mercury with an aqueous solution of silver nitrate. Sonicating different molar ratios of liquid metallic Hg with AgNO results in the formation of pure crystalline phases of solid silver amalgams with uniform morphology. The resulting Hg-Ag amalgams from various comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Hg 2+ + 0. In the case of Fe3O4-Ag 0 nanocomposites, the appearance of a new peak at around 17º probably indicated the formation of an Hg-Ag amalgam (moschellandbergite phase, Ag2Hg3) [48]. The absence of literature on the removal of Hg 2+ from aqueous solutions by the use of Fe3O4-Ag 0 nanocomposites is difficult to support this conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Hg 2+ + 0. In the case of Fe3O4-Ag 0 nanocomposites, the appearance of a new peak at around 17º probably indicated the formation of an Hg-Ag amalgam (moschellandbergite phase, Ag2Hg3) [48]. The absence of literature on the removal of Hg 2+ from aqueous solutions by the use of Fe3O4-Ag 0 nanocomposites is difficult to support this conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Later on, they also achieved pure crystalline Hg-Ag amalgam microspheres with uniform morphology by ultrasonically reacting liquid mercury with an AgNO 3 aqueous solution ( Figure 6). [62] In the study of Kwon and coworkers, [63] another kind of bimetallic alloy Pd n M (n = 1 for M = Mn, Fe, and Co; n = 1, 2, and 3 for M = Ni) nanoparticles (NPs) were synthesized on carbon supports by the sonochemically catalytic reactions of Pd(acetylacetonate) 2 2 and Pt(acetylacetonate) 2 , where the nanoparticles had Pt-enriched surface with Pd and Co forming the core. [64] Certainly, the other sonchemical synthesis of bimetal (e.g., Au/Ag, Au/Pd, Pt/Ru) or even multi-metal nanomaterials (e.g., NiCoPd, Pt/PdNiMo) has been reported as well.…”
Section: Metal and Alloymentioning
confidence: 99%
“…Ag n + Hg 2+ ↔ Ag (n−2) Hg + 2Ag + Harika et al [52] studied the amalgamation reaction by ultrasonically reacting liquid mercury with an aqueous solution of silver nitrate. Although the formation and role of silver nanoparticles is not discussed, the authors observed schachnerite and moschellandsbergite and mixed phases with molar Hg/Ag ratios of 0.665 to 2.…”
Section: Mercury Removal Experimentsmentioning
confidence: 99%
“…There are only few publications on the formation of Hg-Ag amalgams at the nanoscale [52]. Besides the complexity of the reaction, another issue is that the identification of the amalgams by XRD in small concentrations is difficult and only few weak peaks are typically observed; see for example Katok et al [39], who first investigated hyperstoichiometry in a similar system and identified schachnerite.…”
Section: Mercury Removal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation